Web Information Systems Engineering - WISE 2008 Workshops - David Hutchison, Takeo Kanade, Josef Kittler, Jon M. Kleinberg, Friedemann Mattern, John C. Mitchell, Moni Naor, Oscar Nierstrasz, C. Pandu Rangan, Bernhard Steffen, Madhu Sudan, Demetri Terzopoulos, Doug Tygar, Moshe Y. Vardi, Gerhard Weikum, Sven Hartmann, Xiaofang Zhou, Markus Kirchberg. (Springer, 2017)
199 p.